DNA index and anatomical aspects of the micrografting of dragon fruit on different rootstocks - Moreira, Renata Amato; Rodrigues, Mariane Aparecida; Magalhães, Deniete Soares; Pio, Leila Aparecida Salles; Santos, Dalilhia Nazaré dos; Guimarães, Paulo Henrique Sales; Ramos, José Darlan; Pascoal, Moacir (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate the viability of the micrografting of yellow dragon fruit (Selenicereus megalanthus) on different rootstocks, based on DNA content and anatomical analyses. The used rootstocks were: yellow dragon fruit, white dragon fruit (Hylocereus undatus), Saborosa (Selenicereus setaceus) dragon fruit, and the Cebra and Orejona red dragon fruit (Hylocereus polyrhizus) varieties. The experimental design was completely randomized with five treatments and four replicates of five plants. After 30 days of cultivation, the following traits were evaluated: length and diameter of the micrografts and microrootstocks; and root length, percentage of setting, and fresh mass of the micrografts. Flow cytometry analyzes were performed before and after micrografting to verify genetic stability and the occurrence of endoreduplication. In addition, histological sections were made in the micrografting region to verify the connections of vessels and tissues between the graft and the rootstock. Endoreduplication was observed in all treatments. The amount of DNA in the yellow dragon fruit micrograft increased on the red Orejona variety. The presence of vessel connections was verified between the micrografts and microrootstocks. The yellow dragon fruit was also more vigorous when grafted on Orejona. Based on DNA content and anatomical analyses, in vitro yellow dragon fruit micrografting is feasible in all used rootstocks.